O deslocamento inaugural de Laços de família - Carlos Magno Gomes (Estudos de Literatura Brasileira Contemporânea)
This essay presents a reading of women’s place in the tales “Amor” and “Os laços de família”, from the collection Laços de família (1960), by Clarice Lispector. Tak- ing the inaugural lecture idea as a starting point, proposed by Silviano Santiago, it is analyzed the displacement of women outside the family as an original mark of this masterpiece. Based on the concept of heterotopia, by Michel Foucault, the escape of the protagonist is identified as a patriarchal oppression questioning. In both stories, we have a woman in search of a heterotopia of her freedom.